Why people go for antenatal care - Syahrir, Sukfitrianti; Ariantika, Ariantika; Lagu, Abdul Majid HR. (Al-Sihah: The Public Health Science Journal, 2020)
One indicator of the success of development in the health sector is decreased maternal and child mortality. Efforts are being made to reduce maternal mortality rates such as the Making Pregnancy Safer (MPS) program which is a component of the Safe Motherhood initiative. One pillar is the Antenatal Care (ANC) service. This study aims to find out about the factors that influence Antenatal Care (ANC) visits. The variables studied were knowledge, distance of the house, socio-economic status, husband / family support and support of health workforces. This research was a quantitative study using a descriptive analytic approach with a cross sectional method with a population of all third trimester pregnant women who come to check their pregnancy as many as 84 pregnant women obtained in the working area of the Penrang Public Health Center in Pinrang, by using purposive sampling, a sample size of 69 respondents was obtained. The results showed that the level of knowledge, socioeconomic status, husband / family support, and support of health workforces influences antenatal care visits, while the distance of the house did not show a significant effect. We recommend to this health center to improve the provision of information about antenatal services to pregnant women and their families.